(untitled) (Research, Society and Development, 2020)
Zucchini is traditionally used in human consumption, however, the scarcity of information, especially about fertilization and the physiological aspects of this crop, constitutes a major obstacle its cultivation and commercialization. The objective was evaluate the chlorophyll content and gas exchange under cattle bio-fertilization and different sources of nitrogen. The work was carried a randomized block experimental design was used in a factorial scheme 5 x 3 + 1 composed of five cattle bio-fertilizer concentrations, three sources of nitrogen and an additional treatment without nitrogen. The levels of chlorophyll a, b and total, liquid photosynthesis, transpiration, internal CO2 concentration, stomatal conductance, instantaneous water use efficiency, and instantaneous carboxylation efficiency were evaluated. The studied variables were influenced by the interaction between the concentrations of the cattle bio-fertilizer and the nitrogen sources, except for the chlorophyll b content and the instantaneous water use efficiency, which responded only to the nitrogen sources. Ammonium sulfate and urea increased increase the physiological variables evaluated. The combination of ammonium sulfate with bio-fertilizer promoted an increase in chlorophyll a, total chlorophyll, liquid photosynthesis, transpiration, internal carbon concentration, stomatal conductance, and instantaneous carboxylation efficiency. The cattle bio-fertilizer in the soil without nitrogen did not increase the physiological variables evaluated.